The comparison of mental toughness between 2017 SEA Games athletic athletes and 2017 ASEAN Para Games Paralympic athletic athletes - Ahmad, Azrool Afizie; Soh, Kim Geok; Soh, Kim Lam; Ong, Swee Leong; M. N, Mohad Anizu; M. K., Siswantoyo; Sunardi, Jaka; R., Rattaakoses (Wolters Kluwer - Medknow Publications and Media, 2021)
In the context of deepening the mental toughness between athletic athletes, this study aims to identify the mental toughness of athletic athletes involved in 2017 SEA Games and 2017 ASEAN Para Games by comparing the mental toughness level between the normal and Paralympic athletic athletes. This is a descriptive study using purposive sampling method. The overall respondents for this study consist of 50 athletic athletes, with 25 normal and 25 paralympic athletic athletes. Their ages are between 18 to 43 years and they participate in 2017 SEA Games and 2017 ASEAN Para Games. Sports Mental Toughness Questionnaire (SMTQ) developed by Sheard in 2009 has been adapted and used as the study instrument to measure the mental toughness level based on three sub scales namely confident, constancy and control. Study found out that the mental toughness for the 2017 SEA Games athletic athletes and 2017 ASEAN Para Games Paralympic athletic athletes are at high level. Mental toughness value reports are 41.32+5.67 and 43.00+6.88 respectively. However, there is no significant difference reported for the mental toughness between the groups with the value t(48)=-.942, p=.351. The question is does higher mental toughness level of 2017 ASEAN Para Games Paralympic athletic athletes’ acts as their success determinant in the previous 2016 Paralympic Games? This situation shall be explored deeper because in elite level a small difference from the mental toughness aspect is able to change a competition’s final result outcome